METODE ȘI PROCEDEE UTILIZATE ÎN STUDIEREA LIMBII ȘI LITERATURII ROMÂNE - Кібак, Діана Вікторівна (Universitatea de Stat din Moldova; Facultatea de Litere; Departamentul Limba Engleză şi Limba Franceză de Specialitate; Universitatea Pedagogică de Stat „Ion Creangă”; Agenția Universitară a Francofoniei, 2022)
The educational process is a complex system, the result of the interdependence between teaching, learning and assessment, with a well-defined purpose - that of putting into practice the educational ideal, the integral-vocational development of the personality. The main way in which this aspect is achieved is the improvement of the technology, respectively of the forms, methods and means by which the expected result is reached. The didactic technology includes in an unitary whole all the components of the educational process, insisting on the interdependence between the content and all the other aspects, such as: organization, teacher-student feedback, methods, procedures used, etc. Didactic strategies occupy an important place in the didactic technology. By didactic strategy we understand a set of methods and procedures through which the collaboration between teachers and students is carried out in order to teach, learn, but also to evaluate a volume of information, the formation of skills and abilities, the development of the human personality.
Keywords: Strategii didactice interactive; Activitate instructiv-educativă